Driving Energy Efficiency Markets through Municipal Procurement - World Bank (Washington, DC, 2014)
Many of the most successful municipal energy efficient procurement programs around the world London, Mexico City, New York City, and Vienna have been undertaken without any action at the national level. Forward-looking cities can be champions for energy efficiency initiatives today, showing other cities and their national governments how such measures can save money and drive markets. As other cities follow their example, opportunities grow for joint purchasing, strengthening negotiating power to demand lower cost and better quality products. Two strategies have been particularly effective in this area energy efficient purchasing initiatives and energy savings performance contracts. This guidance note outlines the opportunities and barriers to adopting these procurement strategies, provides global lessons and examples, and offers step-by-step guidance on how cities can get started with energy efficient purchasing policies.